2020
DOI: 10.1111/pce.13885
|View full text |Cite
|
Sign up to set email alerts
|

Defence priming in tomato by the green leaf volatile (Z)‐3‐hexenol reduces whitefly transmission of a plant virus

Abstract: Green leaf volatiles (GLVs) can induce defence priming, that is, can enable plants to respond faster or more strongly to future stress. The effects of priming by GLVs on defence against insect herbivores and pathogens have been investigated, but little is known about the potential of GLVs to prime crops against virus transmission by vector insects. Here, we tested the hypothesis that exposure to the GLV Z-3-hexenol (Z-3-HOL) can prime tomato (Solanum lycopersicum) for an enhanced defence against subsequent Tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 69 publications
0
27
0
1
Order By: Relevance
“…The local concentrations of the several GLVs, including 1-penten-3-ol, in the vicinity of stressed plants reach a few ppb. , Heiden et al and Jardine et al observed the high emission of many GLVs, including 1-penten-3-ol and ( Z )-2-hexenal, under stress from pathogen attack or ozone exposure. Common anthropogenic activities like harvesting the cereal and biofuel grasses or residential grass mowing cause significant GLVs emissions that influence the local air quality. Novel agricultural, horticultural, and forestry practices based on the fumigation of plants with GLVs for better resistance against pathogens and abiotic stress will probably increase the GLV emissions. , Thus, GLVs chemistry can play an essential role in the atmosphere and requires thorough attention in atmospheric chemistry and air quality models. Our work increases the chemical-kinetic database for the aqueous-phase reactions that is indispensable for such modeling, as generally postulated in several major reviews. ,, …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The local concentrations of the several GLVs, including 1-penten-3-ol, in the vicinity of stressed plants reach a few ppb. , Heiden et al and Jardine et al observed the high emission of many GLVs, including 1-penten-3-ol and ( Z )-2-hexenal, under stress from pathogen attack or ozone exposure. Common anthropogenic activities like harvesting the cereal and biofuel grasses or residential grass mowing cause significant GLVs emissions that influence the local air quality. Novel agricultural, horticultural, and forestry practices based on the fumigation of plants with GLVs for better resistance against pathogens and abiotic stress will probably increase the GLV emissions. , Thus, GLVs chemistry can play an essential role in the atmosphere and requires thorough attention in atmospheric chemistry and air quality models. Our work increases the chemical-kinetic database for the aqueous-phase reactions that is indispensable for such modeling, as generally postulated in several major reviews. ,, …”
Section: Introductionmentioning
confidence: 83%
“…52−54 Novel agricultural, horticultural, and forestry practices based on the fumigation of plants with GLVs for better resistance against pathogens and abiotic stress will probably increase the GLV emissions. 55,56 Thus, GLVs chemistry can play an essential role in the atmosphere and requires thorough attention in atmospheric chemistry and air quality models. Our work increases the chemical-kinetic database for the aqueous-phase reactions that is indispensable for such modeling, as generally postulated in several major reviews.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been shown that in addition to green leaf alcohols, other groups of GLVs, such as aldehydes and esters, also make the exposed plants defensive ( Kishimoto et al, 2005 ; Frost et al, 2008 ; Hu et al, 2019 ; Su et al, 2020 ). In this study, we tested whether airborne green leaf aldehydes and esters were converted into their corresponding defensive glycosides.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Z3HOL exposure in tea plants creates prime conditions for defense gene expression and plant defense against subsequent infestation by the tea geometrid, Ectropis obliqua ( Xin et al, 2019 ). Z3HOL exposure also provides tomato plants with increased defense against Tomato yellow leaf curl virus transmission by the whitefly, Bemisia tabaci , with primed defense gene expression and metabolite accumulation ( Su et al, 2020 ). The large gap between the limited metabolic changes and the diverse defense responses suggest that the processing of GLVs might be involved in defense induction in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective solutions are being investigated and discussed. Treatment of tomato with (Z)-3-hexenol prepared it for better defense against Tomato yellow leaf curl virus transmitted by whitefly [52]. Spraying with (Z)-3-hexenyl acetate reduced the salt stress in peanuts by a complex genetic mechanism increasing the photosynthetic rate, plant height, and shoot biomass [53].…”
Section: Introductionmentioning
confidence: 99%